2019
DOI: 10.3390/ma12203305
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonds in 2,5-Dihalopyridine-Copper(I) Halide Coordination Polymers

Abstract: Two series of 2,5-dihalopyridine-Cu(I)A (A = I, Br) complexes based on 2-X-5-iodopyridine and 2-X-5-bromopyridine (X = F, Cl, Br and I) are characterized by using single-crystal X-ray diffraction analysis to examine the nature of C2−X2···A–Cu and C5−X5···A–Cu halogen bonds. The reaction of the 2,5-dihalopyridines and Cu(I) salts allows the synthesis of eight 1-D coordination polymers and a discrete structure. The resulting Cu(I)-complexes are linked by C−X···A–Cu halogen bonds forming 3-D supramolecular networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Puttreddy and co-workers also reported similar kinds of observations of C–I···X–C and C–X···I–Cu interactions present in a series of 1D CPs. , These interactions elevate the 1D chains into 2D layer structures. Notash et al revealed that structural design and topology in the case of the self-assembly process can be tailored by altering coordinated anions .…”
Section: Halogen···halogen Interactions In Cpsmentioning
confidence: 60%
“…Puttreddy and co-workers also reported similar kinds of observations of C–I···X–C and C–X···I–Cu interactions present in a series of 1D CPs. , These interactions elevate the 1D chains into 2D layer structures. Notash et al revealed that structural design and topology in the case of the self-assembly process can be tailored by altering coordinated anions .…”
Section: Halogen···halogen Interactions In Cpsmentioning
confidence: 60%
“…In the originals olvated sample, the longer Br = 1.009). [22] Complexes (2)-(4)w ere then synthesized to characterizet he importance of thesehalogen•••halogen interactions. The modifications are summarized in Table 1a nd Figure 1a nd were designed to provide additional insight.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of this setup was prompted by its success in reproducing various features of a range of cobalt complexes [42][43][44] and those involving different metals with pyridine and halopyridine ligands reported in the literature. [45][46][47][48] Thermal Gibbs free energy corrections were extracted from the frequency calculations without the scaling factors. Thus, all reported thermodynamic values correspond to a room temperature (298.15 K) and a normal pressure (1 atm).…”
Section: Methodsmentioning
confidence: 99%